Microsurgical Anatomy of the Vertical Rami of the Superior Longitudinal Fasciculus: An Intraparietal Sulcus Dissection Study. Issue 2 (5th June 2018) - Monroy-Sosa, Alejandro; Jennings, Jonathan; Chakravarthi, Srikant; Fukui, Melanie B; Celix, Juanita; Kojis, Nathaniel; Lindsay, Mark; Walia, Sarika; Rovin, Richard; Kassam, Amin
Abstract: BACKGROUND: A number of vertical prolongations of the superior longitudinal fasciculus, which we refer to as the vertical rami (Vr), arise at the level of the supramarginal gyrus, directed vertically toward the parietal lobe. OBJECTIVE: To provide the first published complete description of the white matter tracts (WMT) of the Vr, their relationship to the intraparietal and parieto-occipital sulci (IPS-POS complex), and their importance in neurosurgical approaches to the parietal lobe. METHODS: Subcortical dissections of the Vr and WMT of the IPS were performed. Findings were correlated with a virtual dissection using high-resolution diffusion tensor imaging (DTI) tractography data derived from the Human Connectome Project. Example planning of a transparietal, transsulcal operative corridor is demonstrated using an integrated neuronavigation and optical platform. RESULTS: The Vr were shown to contain component fibers of the superior longitudinal fasciculus (SLF)-II and SLF-III, with contributions from the middle longitudinal fasciculus merging into the medial bank of the IPS. The anatomic findings correlated well with DTI tractography. The line extending from the lateral extent of the POS to the IPS marks an ideal sulcal entry point that we have termed the IPS-POS Kassam-Monroy (KM) Point, which can be used to permit a safe parafascicular surgical trajectory to the trigone. CONCLUSION: The Vr are a newly conceptualized group of tracts merging along the banks of the IPS, mediating connectivity between the parietal lobe and dorsal stream/SLF. We suggest a refined surgical trajectory to the ventricular atrium utilizing the posterior third of the IPS, at or posterior to the IPS-POS Point, in order to mitigate risk to the Vr and its considerable potential for postsurgical morbidity.